PERANCANGAN GAME THE GHOST HUNTER MENGGUNAKAN METODE COLLISION DETECTION BERBASIS ANDROID - Iscahyadi, Vio Binawan; Hartono, Budi (Information Technology and Telematics, 2018)
ABSTRACT Games or games are things that can be played with certain rules so that there are those who win and some who lose, usually in a context not serious with the aim of refreshing. Playing games can already be said with the life style of today's society. Starting from the age of children to adults even like games. That's all because playing games is a very pleasant thing. Based on these problems researchers intend to build an android-based game inspired by mistic etnic with the title game The Ghost Hunter. The research will use Method Colllision Detection where this application applies visual programing, namely drag and drop with a design that is made as attractive as possible and coding that is not too complicated. Keyword: Lawangsewu, Collision Detection, Adventure, Contruct 2, Android.